Preparation and drying of water-in-oil-in-water (W/O/W) double emulsion to encapsulate soy peptides. (March 2021) - Ying, Xin; Gao, Jiaxing; Lu, Jing; Ma, Changlu; Lv, Jiaping; Adhikari, Benu; Wang, Bo
Graphical abstract: Highlights: W1 /O/W2 double emulsion with a high soy peptides content was prepared. Double emulsion and freeze-dried powder exhibited high encapsulation efficiency. W1 :O ratio, homogenization condition and drying method affected microcapsule quality. A promising delivery matrix to encapsulate hydrophilic ingredients including peptides. Abstract: Soy peptide solution (40%, w/w) was successfully encapsulated in a W1 /O/W2 double emulsion produced by a two-step emulsification process. Polyglycerol polyricinoleate (PGPR) was found to be an effective inner emulsifier compared to Span 60 and lecithin to produce stable W1 /O primary emulsion. The primary emulsion was subsequently emulsified into an outer aqueous phase (W2 ) containing octenyl succinic anhydride (OSA) starch and maltodextrin. The droplet size and encapsulation efficiency of the peptide solution in W1 /O/W2 emulsion were found to depend on the W1 :O ratio, peptide concentration in the inner W1 phase and homogenization condition of the secondary emulsification step. The double emulsion with the highest encapsulation efficiency (>80%) was prepared by: (i) using 40% (w/w) soy peptide solution as W1 phase; (ii) controlling W1 :O ratio at 3:7 (w/w) and (iii) homogenizing the emulsion at 10, 000 rpm for 3 min. The freeze-dried microcapsule powder of W1 /O/W2 emulsion showed higher encapsulation efficiency (>70%) compared to spray-dried one. The freeze-dried microcapsule of W1 /O/W2 double emulsion developed in this study is a promising delivery matrix to encapsulate hydrophilic ingredients including peptides. Fourier-transform infrared spectroscopy (FTIR) spectra of the microcapsule powder indicated good compatibility between peptide and encapsulants.